Characterization of magnetic nanoparticles (Fe3O4) obtained from industrial Iron and steel waste (mill scale) - Nizamoglu, Hasan; Turan, M. Deniz; Sari, Zeynel Abidin (Elsevier, 2026)
Generated as a by-product of steel manufacturing, mill scale mainly consists of iron oxides and has attracted attention as a sustainable source for magnetic nanoparticle synthesis. This study focused on optimizing the mechanical milling method through experimental processes to successfully obtain magnetic nanoparticles from mill scale. During the milling process, parameters such as the mill scale/ball ratio (1/2-1/5), chamber filling ratio (20-50%), milling time (60-1440 min), and initial particle size (-74 to -500 + 250 mu m) were systematically adjusted to achieve nanoscale magnetic particles. The highest magnetic performance was achieved by milling with 0.03 g of zinc stearate for 48 h under a mill scale/ball ratio of 1/5 and a chamber filling ratio of 20%, followed by an additional 60 min of milling in the presence of ozone. Under these conditions, magnetic products with an average particle size of 34 nm were obtained, and structural analysis confirmed that all nanoparticles were in the form of magnetite (Fe3O4). The structural and magnetic properties of nanoparticles synthesized by the treatment of ozone (O3) in mechanical milling have been improved. Comprehensive characterization was performed using XRD, SEM-EDS, Zeta Sizer, VSM, and TEM analyses. The optimized nanoparticles exhibited remarkable magnetic properties, with a coercivity (Hc) of 181.86 Oe, a remanent magnetization (Mr) of 5.14 emu/g, and a saturation magnetization (Ms) of 48.75 emu/g. These results demonstrate that the optimized mechanical milling of waste mill scale is highly effective for producing magnetic nanoparticles.
Keywords: Magnetic nanoparticles; High-energy ball milling (HEBM); Mill scale; Waste